Redesign of E-Commerce Mobile Application with Design Thinking Method: A Case Study of RP2, Online Household Retailer - Natalia Limantara; Renaldi Renaldi; Cynthia Filicia (ComTech: Computer, Mathematics and Engineering Applications, 2021)
RP2 is one of the growing e-commerce sites in Indonesia offering products for home and living. Recently, RP2 launches a mobile application to reach users by using mobile devices to facilitate purchases on RP2. However, the development of this mobile application has not been through a good application development process, so several weaknesses are found. The aim of the research was to redesign the RP2 mobile application using the design thinking method. The method had five stages: empathize, define, ideate, prototype, and test. However, the research only focused on the first four stages. Moreover, a survey using a questionnaire and interviews were done with 34 users of the RP2 mobile application. The research results are a prototype of the RP2 mobile application, which has been tailored to users’ needs and the project owner’s input. Changes have been made to the RP2 mobile application using the design thinking method. Changes are applied in several views, such as home, navigation and notifications, search bar, Product Detail Page (PDP), cart and payment, and profiles. With these changes, it is expected that users of the RP2 mobile application will increase, so the number of transactions through the RP2 mobile application will increase too.